Clinamen, necessity and modern receptions of epicureanism:: The figure of Spinoza - Fytakis, Kyriakos (Trilhas Filosóficas, 2023)
Early modern readings of Epicureanism carried various prejudices and the term epicurean often designated an impious and potentially dangerous thinker. This was the case for Dutch philosopher Baruch Spinoza whose contemporaries compared his doctrine to Epicureanism on several occasions. However, how accurate would it be to affirm that Spinoza’s philosophy belongs to the neo-epicurean tradition? We find such a comparison in many 17th and 18th century texts, especially in works written by critics of his thought, such as François Fénelon or Jean La Placette. Epicurean doctrine on chance was compared to Spinoza’s theory on necessity, but despite the prejudices of the comparison, both Epicurus’s and Spinoza’s philosophies had an important influence on the Enlightenment, namely on French materialists. In our paper, we proceed to an analysis of this comparison and shed light on one of the most influential receptions of Epicurus’s philosophy in modernity. In this perspective, we show their inherent relation and focus more particularly on their modal theories; we thus examine the reasons why- contrary to other cases- the comparison was based less on ethical and mostly on metaphysical matters and we show at what extent it is legitimate.